TYPES OF EXTERNAL CONFLICT REFLECTED BY THE MAIN CHARACTER IN THE “100” COMIC (2021) - I Komang Gede Feriawan (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The aim of this study is to find out the types of external conflict reflected by the main character in the “100” comic on webtoon. External conflict is a conflict that drives story action, namely battles between literary or theatrical figures who have similar forms with elements such as nature or other characters. The data sources of this study were taken from webtoon, that the comic titled consist with 50 episode. This comic was published in 2021 written by Hyeong Eun. This story tells of the life of a young Korean man named Hoyoung Cheon who participates in the Battleground Game, an illegal murder game. He is assigned to find a member of the MPR named Naksu Kim among 100 death row inmates in the game. This study used a descriptive qualitative method and the data were analyzed based on the theory proposed by Kenney (1966), about types of conflict. The result of this study showed the source of external conflict happening in the comic, there were man against man, man against nature, and man against society.